Risk factors associated with contagious caprine pleuro-pneumonia in goats in pastoral areas in the Rift Valley region of Kenya - Kipronoh, K.A.; Ombui, J.N.; Binepal, Y.S.; Wesonga, H.O.; Gitonga, E.; Thuranira, E.; Kiara, Henry K. (Elsevier, 2016)
A cross-sectional study to determine risk factors associated with sero-prevalence of contagious caprine pleuro-pneumonia (CCPP) in goats was carried out between the months of March, 2014 and March, 2015 in Pokot East, Turkana West and Kajiado Central Sub-counties. A semi-structured questionnaire focusing on risk factors for CCPP was completed for each flock whose serum samples were collected. A logistic regression model was developed to assess the association between the risk factors and CCPP sero-positivity. Of the 54 flocks, 49 (90.7%) presented at least one sero-positive animal. Two hundred and four of the 432 goats tested sero-positive at monoclonal antibody based competitive Enzyme-linked immuno-sorbent assay (c-ELISA), hence a sero-prevalence of 47.2% (95% CI = 42.5– 51.9). Previous exposure of flocks to CCPP (p < 0.001, OR = 52.8; CI = 6.45, 432), distant sources of veterinary drugs (p < 0.001, OR = 6.17; CI = 3.41, 11.1), movement of goats to dry season feeding areas (p < 0.001, OR = 4.31; CI = 2.39, 7.75) and markets as a source of new introductions to the flock (p = 0.033, OR = 1.86; CI = 1.05, 3.27) were identified as risk factors significantly associated with CCPP sero-prevalence. The findings provide further evidence supporting the high prevalence and endemic state of the disease in pastoral flocks and hence there is need for adequate measures to be put in place to control the disease effectively.